The Relationship between Power Bases and Influence Tactics of Program Planners - Chan, Siew Meng (2008)
Asymmetrical power relationship between program planners and their superiors could cause substantial amount of constraints for program planners to execute tasks of planning in a democratic manner. Under such situation, program planners are required to negotiate with their superiors by using influence tactics to counterbalance the lop-sided power relationship with their superior. Program planners would also need to acquire power bases and use them as tools to influence their superiors. The main objective of the study was to determine power bases that predict the use of influence tactics by program planners. Along with this objective, the use of influence tactics by program planners, power bases of program planners, the use of influence tactics with respect to personal ctors of program planers and program planners’ perception of importance of power bases in the influence of superiors were also determined. The dependent variables were influence tactics namely pressuring, counteracting, bargaining, reasoning, consulting, appealing and networking tactics. The independent variables were power bases, which were made up of legitimate power, expert power, information control power, uncertainty and ambiguity-coping power, referent power, interpersonal-linkage power and communication-skill power. This is an ex post facto study where data were collected through survey questionnaires. The samples were made up of 367 program planners randomly chosen from 26 teacher training colleges. A total of 264 sets of questionnaires were collected and analyzed. Descriptive statistic was used to describe data pertaining to the use of influence tactics, power bases of program planners, and program planners’ perception of importance of power bases in the influence of superiors. One-way MANOVA was engaged to compare the use of influence tactics of program planners according to their personal characteristics. Multiple Linear Regression was used to determine power bases that predict the use of influence tactics by program planners. The findings of this study indicate that the three most frequently used influence tactics were consulting, reasoning and appealing tactics. Program planners were found to have high power bases with communication-skill power, interpersonal-linkage power and expert power as the three leading power bases. Expert power and legitimate power were perceived as the two most important power bases to influence superiors. The findings of the use of influence tactics with respect to personal factors indicate that there was significant difference in the use of influence tactics among program planners of different gender and age. However, there was no significant difference in the use of influence tactics among program planners of different race, service tenure, academic qualification and level of management in organization. The findings show that among the power bases, interpersonal-linkage power did no predict the use of any influence tactic. However, communication-skill power, referent power and information-control power were significant power bases that predicted the use of pressuring tactic by program planners. Legitimate power and information-control power were significant power bases that predicted the use of counteracting tactic by program planners. Communication-skill power and information-control power were significant power bases that predicted the use of bargaining tactic by program planners. Expert power was the only significant power base that predicted the use of reasoning tactic by program planners. Uncertainty and ambiguity-coping power was the only significant power bases that predicted the use of consulting tactic by program planners. Uncertainty and ambiguity-coping power and information-control power were significant power bases that predicted the use of appealing tactic by program planners. Communication-skill power and referent power were significant power bases that predicted the use of networking tactic by program planners.